Repetitive Construction Scheduling Using Line of Balance (Case Study: One of the 6-Storey Polyclinic Building Construction Project in Batang Regency) - Winata, Dwiki Pandu; Agung Budiwirawan; Muhammad Faizal Ardhiansyah Arifin; Irfandi Saputra Tua Saragi (Jurnal Teknik Sipil dan Perencanaan, 2025)
Repetitive work is often encountered by contractors, so effective planning is needed so that the project can achieve its goals within the set time limit. One aspect of planning is project scheduling, which is a method that is used in construction work. One of the scheduling methods suitable for repetitive construction is a line of balance. Therefore, this research was conducted using the line of balance method on a repetitive multi-story building project to find out whether the line of balance can properly organize project implementation. The results of the analysis and calculations that have been carried out obtained the duration required to complete the construction project of the 6-story polyclinic building for 274 days. The schedule in the project plan takes 308 days to complete the project. By comparing the effectiveness of the time whose duration is at odds with 34 days, the schedule plan using the line of balance method is more effective and efficient in completing the construction project of the 6-story polyclinic building in Batang Regency.